Correlation between Academic Staff Wellbeing and Developing Emotional Intelligence of Students - Tirana, Megi; Memaj, Matilda; Vakaj, Edlira; Pavera, Libor; Pavlíková, Martina (Journal of Education Culture and Society, 2025)
Aim. The main aim of this thesis is to research the correlation between academic staff wellbeing and students’ emotional intelligence development. This study aims to explore how physical health, mental, and emotional health of academic staff affect their capacities to promote emotional intelligence skills like consciousness, sensitivity, and students’ emotional regulation.Methods. This study will adopt a mixed methods approach, combining qualitative and quantitative methods of gathering data to comprehensively explore the correlation between academic staff wellbeing and students’ emotional intelligence development. A sample of 100 professors is available from different departments in higher institutions and will be selected randomly by being layered out. The selection will include various professors related with gender, age, and experience.Results. Quantitative data analysis, by using the correlation Pearson coefficient and regression analysis, discovered a positive moderate correlation between academic staff and emotional intelligence of students (r = 0.52, p